PENGARUH KOMPENSASI, KEPRIBADIAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN ORGANIZATONAL CITIZENSHIP BEHAVIUOR (OCB) SEBAGAI VARIABEL INTERVENING (STUDI PADA PEGAWAI DINAS KESEHATAN KABUPATEN PATI) - Unggul Yudha Hastitama (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
This research has the aim of analyzing the influence of compensation, personality, and work environment on employee performance with Organizational Citizenship Behaviour as an Intervening Variable (study on Health Department Employees at Pati Regency). This research is a study using quantitative approaches. Population 1461 officers. A sample of 145 respondents. Sampling techniques use proportional sampling types and data sources. Primary data sources and secondary data. Test instruments using convergence validity, Average Variance Extracted (AVE), Discriminant Validity, and Construct Reliability. Data analysis using SEM AMOS. The results of testing hypotheses contained in this study, it can be concluded that the study (1) There is a significant positive influence of compensation and personality on employee performance at the Health Department Employee at Pati Regency; (2) There is nothing effect of work environment on employee performance at the Health Department Employee at Pati Regency; (3) There is a significant positive effect of the compensation, personality and work environment on Organizational Citizenship Behaviour at the Health Department Employee at Pati Regency. ; (4) There is a significant positive effect of the Organizational Citizenship Behaviour on employee performance at the Health Department Employee at Pati Regency; (5) Organizational Citizenship Behaviour is able to provide a mediating effect between compensation and personality on employee performance at the Health Department Employee at Pati Regency